2015
DOI: 10.1681/asn.2013101040
|View full text |Cite
|
Sign up to set email alerts
|

Akt Substrate of 160 kD Regulates Na+,K+-ATPase Trafficking in Response to Energy Depletion and Renal Ischemia

Abstract: Renal ischemia and reperfusion injury causes loss of renal epithelial cell polarity and perturbations in tubular solute and fluid transport. Na + ,K + -ATPase, which is normally found at the basolateral plasma membrane of renal epithelial cells, is internalized and accumulates in intracellular compartments after renal ischemic injury. We previously reported that the subcellular distribution of Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…Because AS160 is important for both muscle and adipose GLUT4 trafficking, these models are unable to address tissue-specific contributions. Additionally, AS160 has alternate roles in the heart ( 48 ) and renal epithelial cells ( 49 ), which would have also been affected. Hence, our AR10KO model was designed to be tissue specific and to probe not only the relevance of Rab10, but also of glucose uptake, specifically in the insulin stimulated state.…”
Section: Discussionmentioning
confidence: 99%
“…Because AS160 is important for both muscle and adipose GLUT4 trafficking, these models are unable to address tissue-specific contributions. Additionally, AS160 has alternate roles in the heart ( 48 ) and renal epithelial cells ( 49 ), which would have also been affected. Hence, our AR10KO model was designed to be tissue specific and to probe not only the relevance of Rab10, but also of glucose uptake, specifically in the insulin stimulated state.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Na–K‐ATPase plays an additional significant role in altered tubular sodium handling after I/R, particularly in the PT (especially in the S3 segment) and the outer medullary TAL, which are known to be the segments most affected by ischemic insult (Alves et al. ). In our study, immunohistochemistry showed that Na–K‐ATPase staining seemed weaker in the OM alone in I/R kidneys compared to both sham‐ and rIPeC‐treated I/R kidneys, indicating that regulation of Na–K‐ATPase in response to I/R and rIPeC is more confined to this kidney zone compared to the rest of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The Na + -K + -ATPase is a ubiquitous transmembrane protein that transports three Na + out of and two K + into the cell for maintaining cell membrane potential and intracellular ion homeostasis [4]. Numerous studies indicate the involvement of Na + -K + -ATPase in development of many diseases, including renal injury [5,6]. For example, decreased Na + -K + -ATPase activity has been reported in injured kidney cells, renal damage animal models and even in renal patients [5,7,8].…”
Section: Introductionmentioning
confidence: 99%